The Rise and Fall of the Segway: Lessons for the Social Adoption of Future Transportation. Issue 2 (1st June 2019) - Clark, Andrew V.; Atkinson-Palombo, Carol; Garrick, Norman W.
Abstract : Once posited as a revolutionary transportation technology, the Segway never took off as some expected because the social acceptance of the technology was not considered in a systematic manner. Using a framework for social acceptance of technology borrowed from the literature on renewable energy, we examine how social, economic, and environmental costs of the Segway, along with regulatory issues presented barriers to implementation. High prices, legislative and spatial issues, and a lack of appeal to consumers presented challenges to acceptance. This case study provides a timely reminder of the multifaceted and complex nature of social acceptance that will need to be applied to future innovations, such as autonomous vehicles, to better understand factors that need to be considered for them to be embraced by society.